CLUE: a randomized comparative effectiveness trial of IV nicardipine versus labetalol use in the emergency department - W. Frank Peacock; Joseph Varón; Brigitte M. Baumann; Pierre Borczuk; Chad Cannon; Abhinav Chandra; David Cline; Deborah B. Diercks; Brian Hiestand; Amy P. Hsu; P. Jois-Bilowich; Brian Kaminski; et al. (2011)
Abstract Introduction Our purpose was to compare the safety and efficacy of food and drug administration (FDA) recommended dosing of IV nicardipine versus IV labetalol for the management of acute hypertension. Methods Multicenter randomized clinical trial. Eligible patients had 2 systolic blood pressure (SBP) measures ≥180 mmHg and no contraindications to nicardipine or labetalol. Before randomization, the physician specified a target SBP ± 20 mmHg (the target range: TR). The primary endpoint was the percent of subjects meeting TR during the initial 30 minutes of treatment. Results Of 226 randomized patients, 110 received nicardipine and 116 labetalol. End organ damage preceded treatment in 143 (63.3%); 71 nicardipine and 72 labetalol patients. Median initial SBP was 212.5 (IQR 197, 230) and 212 mmHg (IQR 200,225) for nicardipine and labetalol patients ( P = 0.68), respectively. Within 30 minutes, nicardipine patients more often reached TR than labetalol (91.7 vs. 82.5%, P = 0.039). Of 6 BP measures (taken every 5 minutes) during the study period, nicardipine patients had higher rates of five and six instances within TR than labetalol (47.3% vs. 32.8%, P = 0.026). Rescue medication need did not differ between nicardipine and labetalol (15.5 vs. 22.4%, P = 0.183). Labetalol patients had slower heart rates at all time points ( P < 0.01). Multivariable modeling showed nicardipine patients were more likely in TR than labetalol patients at 30 minutes (OR 2.73, P = 0.028; C stat for model = 0.72) Conclusions Patients treated with nicardipine are more likely to reach the physician-specified SBP target range within 30 minutes than those treated with labetalol. Trial registration ClinicalTrials.gov: NCT00765648